Episode 1: The Russian Challenge in the Black Sea and the Arctic - Kardon, Isaac B.; Petersen, Michael B. (U.S. Naval War College Digital Commons, 2023)
Admiral Jamie Foggo (USN, ret) discusses Russian sea power in the Black Sea and Arctic regions with Dr. Michael Petersen, Director of the Russia Maritime Studies Institute" Guest: Admiral James G. Foggo III, USN (Ret.), is dean of the Navy League of the United States Center for Maritime Strategy. A submarine officer, he is a former commander of U.S. Naval Forces Europe and Africa and Allied Joint Force Command, Naples. He commanded BALTOPS in 2015 and 2016 and Exercise TRIDENT JUNCTURE in 2018. Co-Host: Michael Petersen, PhD, is the director of the Russia Maritime Studies Institute and professor at the U.S. Naval War College, Center for Naval Warfare Studies. Prior to his appointment at NWC, he served at the Defense Intelligence Agency and the National Security Council. https://digital-commons.usnwc.edu/seapower/1000/thumbnail.jpg